Advancing respiratory–cardiovascular physiology with the working heart–brainstem preparation over 25 years. (7th April 2022) - Paton, Julian F. R.; Machado, Benedito H.; Moraes, Davi J. A.; Zoccal, Daniel B.; Abdala, Ana P.; Smith, Jeffrey C.; Antunes, Vagner R.; Murphy, David; Dutschmann, Mathias; Dhingra, Rishi R.; McAllen, Robin; Pickering, Anthony E.; et al.
Abstract: Twenty‐five years ago, a new physiological preparation called the working heart–brainstem preparation (WHBP) was introduced with the claim it would provide a new platform allowing studies not possible before in cardiovascular, neuroendocrine, autonomic and respiratory research. Herein, we review some of the progress made with the WHBP, some advantages and disadvantages along with potential future applications, and provide photographs and technical drawings of all the customised equipment used for the preparation. Using mice or rats, the WHBP is an in situ experimental model that is perfused via an extracorporeal circuit benefitting from unprecedented surgical access, mechanical stability of the brain for whole cell recording and an uncompromised use of pharmacological agents akin to in vitro approaches. The preparation has revealed novel mechanistic insights into, for example, the generation of distinct respiratory rhythms, the neurogenesis of sympathetic activity, coupling between respiration and the heart and circulation, hypothalamic and spinal control mechanisms, and peripheral and central chemoreceptor mechanisms. Insights have been gleaned into diseases such as hypertension, heart failure and sleep apnoea. Findings from the in situ preparation have been ratified in conscious in vivo animals and when tested have translated to humans. We conclude by discussing potential future applications of the WHBP including two‐photon imaging of peripheral and central nervous systems and adoption of pharmacogenetic tools that will improve our understanding of physiological mechanisms and reveal novel mechanisms that may guide new treatment strategies for cardiorespiratory diseases. Abstract : Abstract figure legend The working heart–brainstem preparation (WHBP) was first published in 1996 and since that time has revealed novel mechanisms in the generation of breathing rhythms and patterns, autonomic control of the heart and circulation, and the physiological relevance of the coupling between respiratory and cardiovascular systems. This review brings together an international cohort of authors who have adopted the WHBP, to highlight some of the major advances and discoveries made using this in situ arterially perfused preparation.